Peningkatan Kompetensi Teknologi: Pelatihan Pengelolaan Laboratorium Komputer untuk Tenaga Pendidik di Pulau Lengudi - Yuli Endra, Robby (CV. Alfa Pustaka, 2024)
The advancement of information technology requires educators to manage computer laboratories as a technology-based learning facility. However, educators in remote areas, such as Lengudi Island, face various challenges in managing these laboratories. This article discusses training aimed at enhancing educators' competencies in hardware, software, and local area network (LAN) management. The training was conducted through preparation, hands-on practice, mentoring, and evaluation. Results indicated a 40% increase in participants' understanding based on pre-test and post-test scores and a 75% improvement in laboratory functionality. This article concludes that the training successfully enhanced educators' competencies and recommends further training to sustain the program.